Working together apart? building a knowledge-sharing culture for global virtual teams - Zakaria, Norhayati; Amelinckx, Andrea; Wilemon, David (Blackwell Publishing Ltd, 2004)
A new impetus for greater knowledge-sharing among team members needs to be emphasized due to the emergence of a significant new form of working known as ‘global virtual teams’.As information and communication technologies permeate every aspect of organizational life and impact the way teams communicate, work and structure relationships, global virtual teams require innovative communication and learning capabilities for different team members to effectively work together across cultural, organizational and geographical boundaries.Whereas information technology-facilitated communication processes rely on technologically advanced systems to succeed, the ability to create a knowledge-sharing culture within a global virtual team rests on the existence (and maintenance) of intra-team respect, mutual trust, reciprocity and positive individual and group relationships.Thus, some of the inherent questions we address in our paper are: (1) what are the cross-cultural challenges faced by global virtual teams?; (2) how do organizations develop a knowledge sharing culture to promote effective organizational learning among culturally-diverse team members? and; (3) what are some of the practices that can help maximize the performance of global virtual teams? We conclude by examining ways that global virtual teams can be more effectively managed in order to reach their potential in this new interconnected world and put forward suggestions for further research.